Clinical features and outcomes of patients with preeclampsia and eclampsia at Gondar University hospital, Amhara, Ethiopia 2021 - Tamalew Alemie; Asmamaw Abebe; Ousman Adal; Aklilu Azazh; Destaw Endeshaw (Elsevier, 2023)
Objective: The aim of this study was to investigate the clinical features, and treatment outcome of women with preeclampsia and eclampsia at Gondar University Comprehensive Specialized Hospital in Amhara, Northern Ethiopia, in 2021. Methods: An institutional-based retrospective chart review was conducted at Gondar University Specialized Hospital from March to June 2021. The study participants were chosen using a simple, systematic random sampling method. A pretested check list was used to collect data from medical records. The collected data was coded, entered into Epi-data version 4.6, and exported to SPSS version 26 for descriptive and inferential analysis. A Fisher's exact test was used to determine statistically significant factors at a p-value of < 0.05. Results: Of the 311 study participants, more than half (53 %) of mothers have illiterate, nearly half (49.8 %) had preeclampsia with severe features. Eclampsia accounted for 18.6 % of females in the study setting. For various reasons, more than half of the mothers required immediate intervention to terminate the pregnancy via cesarean section. Unfavorable maternal outcomes were present in more than 25 % of cases; the observed unfavorable maternal outcomes were aspiration pneumonia (10.6 %), hemolytic elevated liver function test and low platelet count syndrome (8.7 %), and maternal death (0.6 %). The severity of the disease, mode of delivery, aspartate transaminase, gravidity, gestational age, and antenatal care were all statistically significant predictors of pregnancy outcome. Conclusion: The prevalence of unfavorable maternal and perinatal outcomes of preeclampsia and eclampsia is considerable in the study area. To prevent these perinatal and postnatal effects, maternal outcomes of pregnancy, antenatal care services, emergency obstetrics, and new born care should be expanded and strengthened.